The mechanism of sex ratio adjustment in a pollinating fig wasp - Raja, Shazia (The Royal Society, 2008)
Sex ratio strategies in species subject to local mate competition (LMC), and in particular their fit to quantitative theoretical predictions, provide insight into constraints upon adaptation. Pollinating fig wasps are widely used in such studies because their ecology resembles theory assumptions, but the cues used by foundresses to assess potential LMC have not previously been determined. We show that Liporrhopalum tentacularis females (foundresses) use their clutch size as a cue. First, we make use of species ecology (foundresses lay multiple clutches, with second clutches smaller than first) to show that increases in sex ratio in multi-foundress figs occur only when foundresses are oviposition site limited, i.e. that there is no direct response to foundress density. Second, we introduce a novel technique to quantify foundress oviposition sequences and show, consistent with the theoretical predictions concerning clutch size-only strategies, that they produce mainly male offspring at the start of bouts, followed by mostly females interspersed by a few males. We then discuss the implications of our findings for our understanding of the limits of the ability of natural selection to produce ‘perfect’ organisms, and for our understanding of when different cue use patterns evolve.